Clinical Significance of Low-Density Granulocytes in Acute Pancreatitis - Jiren Wang; Xinwen Chen; Youli Ke; Nannan Zhu; Jiejie Zhu; Hao Ding; Linlin Pan; Chenao Zhang; Xingyu Liu; Yumei Wu; Huizhong Gan; Qiao Mei (Mediators of Inflammation, 2025)
Conclusion: Elevated peripheral LDGs levels in AP patients are associated with disease activity.